The Chemokine Receptor CCR5 Links Memory CD4+ T Cell Metabolism to T Cell Antigen Receptor Nanoclustering - Blanco, Raquel; Gómez de Cedrón, Marta; Gámez-Reche, Laura; Martín-Leal, Ana; González-Martín, Alicia; Lacalle, Rosa A.; Ramírez de Molina, Ana; Mañes, Santos (Frontiers in Immunology, 2021)
The inhibition of anabolic pathways, such as aerobic glycolysis, is a metabolic cornerstone of memory T cell differentiation and function. However, the signals that hamper these anabolic pathways are not completely known. Recent evidence pinpoints the chemokine receptor CCR5 as an important player in CD4+ T cell memory responses by regulating T cell antigen receptor (TCR) nanoclustering in an antigen-independent manner. This paper reports that CCR5 specifically restrains aerobic glycolysis in memory-like CD4+ T cells, but not in effector CD4+ T cells. CCR5-deficient memory CD4+ T cells thus show an abnormally high glycolytic/oxidative metabolism ratio. No CCR5-dependent change in glucose uptake nor in the expression of the main glucose transporters was detected in any of the examined cell types, although CCR5-deficient memory cells did show increased expression of the hexokinase 2 and pyruvate kinase M2 isoforms, plus the concomitant downregulation of Bcl-6, a transcriptional repressor of these key glycolytic enzymes. Further, the TCR nanoclustering defects observed in CCR5-deficient antigen-experienced CD4+ T cells were partially reversed by incubation with 2-deoxyglucose (2-DG), suggesting a link between inhibition of the glycolytic pathway and TCR nanoscopic organization. Indeed, the treatment of CCR5-deficient lymphoblasts with 2-DG enhanced IL-2 production after antigen re-stimulation. These results identify CCR5 as an important regulator of the metabolic fitness of memory CD4+ T cells, and reveal an unexpected link between T cell metabolism and TCR organization with potential influence on the response of memory T cells upon antigen re-encounter.